Frailty as a Key Predictor of Malnutrition among Older Adults with Swallowing Problems: Frailty as a Key Predictor of Malnutrition among Older Adults with Swallowing Problems - Sirikul, Saowaluk; Roopsawang, Inthira; Aree-Ue, Suparb (Pacific Rim International Journal of Nursing Research, 2024)
Geriatric syndrome—frailty—has a more significant influence on the health of older, pre-frail and frail older adults who tend to have a poor nutritional status or develop severe malnutrition. Investigation of frailty and its association with malnutrition and swallowing problems is limited in older Thais. This cross-sectional study examined the association among frailty and other associated factors with malnutrition in older adults with swallowing problems. A purposive sampling method was employed to recruit 120 participants who met the specified inclusion criteria. Data were obtained from older adults who visited and received medical services at the rehabilitation department of a university hospital in Bangkok, Thailand, from July 2022 to February 2023. The instruments included the Demographic and Health Information Record Form, Mini Nutritional Assessment Short-Form - MNA® Elderly, Reported Edmonton Frail Scale-Thai Version, and Modified Barthel Activities of Daily Living Index. Data were analyzed using descriptive statistics and multiple logistic regression. The findings indicated that 82.5% of participants were frail, and approximately 30% and 80.0% presented with dependence and at-risk or malnutrition, respectively. Frailty, age, comorbidities, a history of aspiration, and activities of daily living could predict malnutrition, accounting for 71.7%. Significantly, frailty demonstrated a 4.47-fold increased risk of malnutrition, while dependence on activities of daily living had a 6.41-fold increased risk of malnutrition among this population. The findings of this study provide valuable insights for healthcare professionals, especially gerontological nurse practitioners, to raise awareness of the early detection of frailty, swallowing problems, and potential risks of malnutrition, together with promoting daily activity in older adults across settings. Implementing comprehensive management to improve swallowing and physical function in older adults at risk of frailty and malnutrition may enable gerontological nurse practitioners to strengthen professional care. By doing so, maintaining nutritional health among these populations can be achieved.